The energy of Bianchi type I and II universes in teleparallel gravity - So, L. L.; Vargas, T. (Physical Soc Republic China, 2005)
For certain models, the energy of the universe, which includes the energy of both matter and the gravitational fields, is obtained by using the quasi-local energy-momentum in teleparallel gravity. It is shown that, in the case of the Bianchi type I and II universes, not only the total energy but also the quasi-local energy-momentum for any region vanishes independently of the three dimensionless coupling constants of teleparallel gravity.